2009
DOI: 10.1093/hmg/ddp123
|View full text |Cite
|
Sign up to set email alerts
|

Short 42 C heat shock induces phosphorylation and degradation of Cdc25A which depends on p38MAPK, Chk2 and 14.3.3

Abstract: The effects of heat shock (HS; 42 degrees C) on the cell cycle and underlying molecular mechanisms are astonishingly unexplored. Here, we show that HS caused rapid Cdc25A degradation and a reduction of cell cycle progression. Cdc25A degradation depended on Ser75-Cdc25A phosphorylation caused by p38MAPK and Chk2, which phosphorylated Ser177-Cdc25A that is specific for 14.3.3 binding. Upon HS, Cdc25A rapidly co-localized with 14.3.3 in the perinuclear space that was accompanied with a decrease of nuclear Cdc25A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…In S-phase, cells were arrested a second time, because meanwhile Cdc25B became degraded and Chk2 strongly activated (39). The activity of Chk1 and Chk2 was reflected by the increased phosphorylation levels of Ser75 and Ser177 of Cdc25A, respectively (23,40). The temporally separated effects on cell cycle inhibition were probably due to distinct anti-neoplastic compounds present in the petroleum ether extract.…”
Section: Discussionmentioning
confidence: 96%
“…In S-phase, cells were arrested a second time, because meanwhile Cdc25B became degraded and Chk2 strongly activated (39). The activity of Chk1 and Chk2 was reflected by the increased phosphorylation levels of Ser75 and Ser177 of Cdc25A, respectively (23,40). The temporally separated effects on cell cycle inhibition were probably due to distinct anti-neoplastic compounds present in the petroleum ether extract.…”
Section: Discussionmentioning
confidence: 96%
“…Accumulating evidence has shown that HS can cause G 1 and G 2 /M arrest [54][55][56] p53-dependent transcription of p21 and p38 MAPK dependent CDC25A degradation were demonstrated as mechanisms for HS-induced G 1 arrest [57]. However, the molecular mechanism underlying G 2 /M checkpoint activation in cells exposed to HS had not been extensively investigated.…”
Section: Heat Induced Dna Damage and Cell Cycle Checkpointsmentioning
confidence: 99%
“…S99, S148, S178, S192, S204, S206, T226, S234, S359, T561, S567, T569 [60,156,157,162] Cdk1-cyclin B S18, S40, S88, S116, S261, S283, S321 [149,151,167] Chk1 S76, S124, S178, T507 [168][169][170][171][172][173]200] Chk2 S124, S278 [173,175] Casein Kinase 1ε S82 [199] Casein Kinase 1α S79, S82 [198] p38 S76, S124 [168,175] GSK-3β S76 [193,194] NEK11 S82, S88 [187] Plk3 S80 [193,194] Cdk1-cyclinB S50, S160, S321 [135,136,246] Chk1 S151, S230, S323, S563 [236,238,239] Aurora S353 [124] Casein Kinase 2 S186, S187 [235] JNK S101, S103 [280] MEK/ERK S249 [259] p38 S323 [208] MK2 S323 [210] Plk1 T167, S209, T404, S465 [136] Cdk1/cyclin B T48, T67, S122, T130, S168, S214 [42,143,145,246] Chk1 S216, S247, S263 [219-221, 225, 226] Chk2 S216 [209,242] Casein Kinase 2 T236 …”
Section: Speciesmentioning
confidence: 99%
“…[168,169,[174][175][176] In the original cloning of human Cdc25A. [37], there are several substitutions in the N-terminus (Accession: AAA58415.1) and a one residue gap corresponding to residue R12 in all other full length human Cdc25A sequences in the NCBI database (Accession: P30304).…”
Section: G1/s and Intra-s Checkpointsmentioning
confidence: 99%
See 1 more Smart Citation